Small business digital transformation in the USA in the conditions of COVID-19 pandemic - N. E. Petrovskaya; S. S. Kiseleva (Вестник университета, 2024)
The purpose of the study is to examine small businesses digital transformation in the US in the context of the COVID-19 pandemic. The subject of the study is the pandemic impact on small businesses digitalization in the US. The coronavirus had a huge impact on the small business sphere, influenced the distribution of these businesses by industry, their employment ratio, the socio-demographic characteristics of small business owners, and accelerated digitalization in order to adapt to new conditions and overcome the economic crisis. It was hypothesized that the coronavirus pandemic had a greater impact on the services market than on the goods market. The authors investigate what changes occurred in small businesses as the pandemic result and what digital technologies were applied to adapt to the new conditions. The COVID-19 pandemic triggered the digitalization that had already begun earlier, increasing digital transformation in the small business sector from an average of 30 to 55 %. According to 86 % of U.S. small business owners, it was the use of technology that helped them survive the pandemic. As the study result, the authors concluded that manufacturing companies have started using digital platforms more frequently than businesses related to their services. Hence, the hypothesis put forward is not confirmed. The COVID-19 pandemic has severely impacted small businesses around the world. The American experience can help to understand what strategies and technologies were used to adapt to the new environment and retain business.